THE ADOPTION OF A NEW MODEL OF ISLAMIC CORPORATE SOCIAL RESPONSIBILITIES (I-CSR) IN MITIGATING THE LIKELIHOOD OF FRAUDULENT FINANCIAL REPORTING - Dr. Amri Mohamad; Dr. Nik Zam Nik-Wan; Dr. Normaizatul Akma Saidi; Noraida Saidi (International Journal of Accounting, Finance and Business, 2022)
Financial reporting issues have been debated endlessly by previous studies using various theories and predictors. Besides, Malaysian Code of corporate governance have been revised few times following the fall of high-profile corporate scandals like Enron in 2007, 2012 and 2017 respectively. However, these revisions seem unable to curb the occurrence of fraudulent financial reporting in Malaysia. As a proof, recently there is a case of false submission of financial statement to Bursa Malaysia. Thus, the objective of this study is to fill in the gaps in the previous literatures by proposing that the new CSR model from Islamic perspective known as Islamic Corporate Social Responsibilities (I-CSR) in mitigating the likelihood of fraudulent financial reporting in Malaysia. A secondary literature review was conducted to identify the Islamic elements which can be embedded into CSR framework. This study has identified four Islamic elements from the previous literatures namely Islamic economic responsibilities, Islamic legal responsibilities, Islamic ethical responsibilities and Islamic philanthropic responsibilities. Thus, this study proposed that companies with I-CSR in practices less likely to engage in any fraudulent financial reporting activities. This study provides important insights to the practitioners and regulators in identifying the suitable mechanism to reduce the likelihood of fraudulent financial reporting by incorporating Islamic elements into CSR disclosure framework.